Clinical Characteristics and Risk Factors for Evisceration in Trauma-Dominant Orbital Cellulitis: A 10-Year Review - Jiang, Zhaoxin; Zhongliu, Xueying; Ding, Xiaohu; Yang, Yao; Duan, Fang; Lin, Xiaofeng (Frontiers in Medicine, 2022)
Purpose: To analyze the clinical characteristics of trauma-dominant orbital cellulitis (OC) and evaluate the risk factors associated with evisceration. Methods: This retrospective study included inpatients diagnosed with orbital cellulitis at the Zhongshan Ophthalmic Center between January 2010 and December 2020. The demographic features, etiology, clinical characteristics, microbiological isolates, and risk factors associated with evisceration were analyzed. Results: Among 148 consecutive subjects (n=148, 148 eyes), the mean age was 42.07 ± 20.35 years and 70.27% were male. Penetrating globe injuries were the most common (52.03%). No light perception (NLP) was recorded in 50% of patients on admission. Endophthalmitis was observed in 103 cases (69.59%), intraocular foreign bodies (IOFB) were detected in 43 cases (29.05%), and total corneal melting was observed in 31 cases (20.95%). Sixty patients (40.54%) underwent evisceration. Logistic regression analysis showed that total corneal dissolution (odds ratio [OR] =83.019, P=0.000), IOFB (OR=3.402, P=0.016), and NLP (OR=0.185, P=0.001) were risk factors for evisceration. Microorganism detection showed that Pseudomonas aeruginosa and Bacillus cereus were the leading pathogens. Conclusion: Among hospitalized trauma-dominant OC patients, middle-aged men were the major subjects and penetrating globe injury was the major cause. Significant complications such as complete visual loss and evisceration were unavoidable in many patients with OC in the current study. NLP, IOFB, and total corneal melting were the risk factors for evisceration.